Characteristics of Breast Cancer Patients Undergoing Radiotherapy at the H. Adam Malik Central General Hospital Medan in 2020-2021 - Luthfi Aidil Rizal Lubis; Muhammad Fauzi Siregar (Talenta Publisher, 2025)
Background: Breast cancer can affect both women and men, originating in the mammary glands, fatty tissue, or connective tissue of the breast. Radiation therapy is a key treatment option applicable at nearly all disease stages. Objective: To examine the characteristics of breast cancer patients receiving radiotherapy, focusing on body mass index (BMI), histopathological classification, breastfeeding history, previous treatments, clinical stage, and age. Methods: This descriptive observational study involved total sampling and secondary data from medical records. Univariate analysis was performed. Out of 120 reviewed records, 43 met the inclusion criteria. Results: Most patients had normal nutritional status (48.8%) and were diagnosed with Invasive Ductal Carcinoma (74.4%). The majority had a history of breastfeeding (95.3%), underwent chemotherapy beforehand (59.4%), were at clinical stage IIB (41.9%), and belonged to the early elderly age group (39.5%). Conclusion: The primary characteristics of breast cancer patients undergoing radiotherapy at Haji Adam Malik General Hospital, Medan (2020–2021), include normal BMI, Invasive Ductal Carcinoma, breastfeeding history, prior chemotherapy, stage IIB disease, and early elderly age. These findings underscore the importance of early detection, managing modifiable risk factors, and integrated treatment approaches for improved outcomes.